Eucalyptus globulus Labill. Essential Oil Effect on the Attachment of Oral Bacteria to Hydroxyapatite and Biofilm Formation - Hardou-Belhocine, Kahina; Brahmi, Fatiha; Grenier, Daniel; Mouhoubi, Khokha; Madani, Khodir; Boulekbache-Makhlouf, Lila (Current Bioactive Compounds, 2025)
BackgroundPeriodontal disease and dental caries are two oral illnesses that are significantly influenced by microorganisms, hence the usefulness of finding natural substances to inhibit them.ObjectiveThis study aimed to assess the Eucalyptus globulus Labill. leaf and fruit essential oils effect against Streptococcus mutans, Streptococcus sobrinus, Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Fusobacterium nucleatum, and Candida albicans to study their anticariogenic and antiperiodonto pathogenic activities.MethodsThese activities were evaluated according to the determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC), anti-biofilm effects, and the impact on the adhesion to hydroxyapatite, a main component of the tooth.ResultsBoth leaf and fruit essential oils showed strong antibacterial activity against anaerobic bacteria: F. nucleatum (MIC of 0.012%) and P. gingivalis (MIC of 0.025%). Anticarcinogenic activity also showed MIC values of 0.06% against S. mutans and, 0.5% against S. sobrinus, and appropriate antifungal activity against C. albicans. It is interesting to note that both oils showed a significant inhibitory property to biofilm formation by the different studied species and significantly reduced the adhesion capacity of S. mutans and S. sobrinus to the hydroxyapatite surface at very low concentrations of 0.12 and 0.5% for S. mutans and S. sobrinus, respectively.ConclusionThese results highlight the strong potential of E. globulus essential oils as antimicrobial and antibiofilm agents, as well as their ability to inhibit bacterial adhesion, which is promising for the prevention of dental caries and plaque. This implies that E. globulus may be a new alternative source of substances of medicinal interest that can be used in the pharmaceutical industry to produce antimicrobial agents against dental caries and oral infectious diseases.
Keywords: biofilm